IT sparks : User-based approach in the improvement of lighting design of IT Parks in Metro Manila - Labrador, Althea Lisbet O.; Navarra, Nappy L (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Lighting design is one of the most important landscape elements of parks and other recreational areas, as it has a substantial effect on its users. A suitable design of lighting leads and guides its users on the usage of the park and its facilities during night time. Lighting can also affect a person's perception; it can be in terms of aesthetics, legibility, way finding, sense of place, and security and safety. Most of the problems with lighting designs on public areas like parks are the lack of consideration to its users, especially for BPO employees or employees working on graveyard shift. In designing parks, the most beneficial and significant factor to consider is the users' perception in order for them to fully optimize the park. Night time has a bigger impact when it comes to experience, much more different than daytime since some of the users' perception is at the same time, facilities could heightened. The research aims to examine and evaluate existing urban park which houses or serves residents of IT/BPO companies to determine its use beyond daytime. The study intends to study how the perception of the park users influences their use during the night and how lighting design affects night time park usage. The research is conducted through measured observation and processing of the experience of park users. In contribution to the Field of Landscape Architecture design, research and guidelines, this study offers recommendation in improving the designs of urban parks, allowing them to accommodate for night time use. Also, this serves as a basis in designing landscape areas that are open to the public during night time and can accommodate companies that have graveyard shifts.
includes appendices.
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman